2022
DOI: 10.1002/dac.5258
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐band dual‐sense broadband circularly polarized parasitic ring loaded monopole antenna for satellite applications

Abstract: A novel-shaped dual-band circularly polarized (CP) monopole antenna is proposed. Two parasitic strips are fabricated under the unique shaped monopole element to get dual broad operation bands. The proposed antenna is fabricated on the FR4 substrate with the specification of the substrate dimension 40 mm  30 mm, ε r ¼ 4:4, h ¼ 1:6 mm, and loss tangent tan δ ¼ 0:02. The parasitic elements are responsible to improve the current distribution I x and I y on the surface. Two CP modes are developed for orthogonally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A dual-CP antenna can generate right-and left-hand circular polarization (RHCP and LHCP), reducing the number of required antennas and enlarging the polarization diversity. 12,13 Therefore, antennas with dual-CP radiation have been extensively explored. [14][15][16][17][18][19][20] The ME-dipole antenna 14 combined two dipoles and the crossed-dipole antenna 15 integrated quadrature coupler are the easy ways to realize wideband dual-CP radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dual-CP antenna can generate right-and left-hand circular polarization (RHCP and LHCP), reducing the number of required antennas and enlarging the polarization diversity. 12,13 Therefore, antennas with dual-CP radiation have been extensively explored. [14][15][16][17][18][19][20] The ME-dipole antenna 14 combined two dipoles and the crossed-dipole antenna 15 integrated quadrature coupler are the easy ways to realize wideband dual-CP radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have proposed some UWB CP antennas by utilizing various structures and techniques in Geng et al, 8 Oteng Gyasi et al, 9 Kumar et al, 10 and Tang et al 11 However, all these designs can only realize single polarization CP radiation. A dual‐CP antenna can generate right‐ and left‐hand circular polarization (RHCP and LHCP), reducing the number of required antennas and enlarging the polarization diversity 12,13 . Therefore, antennas with dual‐CP radiation have been extensively explored 14–20 .…”
Section: Introductionmentioning
confidence: 99%
“…In references, 14–17 coplanar strip, simple strip, slot and half cutting CP antenna techniques, and inverted L‐ shaped PS with microstrip line had been developed for CP radiation. Semicircular patch antenna, 18 metal ridge septum with rectangle and triangle cascade, 19 trapezoidal monopole antenna, 20 two parasitic strips loaded CP antenna, 21 coplanar waveguide feeded T ‐shaped monopole antenna with inverted L ‐shaped grounded stub, 22 modified rectangular monopole, asymmetric ground plane, L ‐shaped strip with CPW feed, 23 and a DRA for circular polarization 24 were implemented for broadband, dual‐band, and dual‐sense applications. From the above literature survey, it is observed that the ARBW is improved with large antenna size.…”
Section: Introductionmentioning
confidence: 99%
“…rectangle and triangle cascade, 19 trapezoidal monopole antenna, 20 two parasitic strips loaded CP antenna, 21 coplanar waveguide feeded T-shaped monopole antenna with inverted L-shaped grounded stub, 22 modified rectangular monopole, asymmetric ground plane, L-shaped strip with CPW feed, 23 and a DRA for circular polarization 24 were implemented for broadband, dual-band, and dual-sense applications. From the above literature survey, it is observed that the ARBW is improved with large antenna size.…”
mentioning
confidence: 99%
“…38 Gas sensors are able to detect their presence and type, and they are very useful in industries. 39,40 The various methods used in the papers include rat race coupled, 41 parallel coupled, 42 phase variation, 43 near-field self-injection-locked and spiral bandgap, 44 GaAs monolithic microwave integrated circuit, 45 coplanar waveguide-fed wearable antenna, 46 ring loaded monopole antenna, 47 wireless networks, 48,49 and split-ring resonators (SRR). [50][51][52] In Ebrahimi et al, 53 the dielectric properties of the samples are determined using a complementary SRR (CSRR) structure.…”
Section: Introductionmentioning
confidence: 99%